Marketing Strategy Planning to Gain Competitive Advantage (Case Study in Triseason Holiday) - Oktina, SE, Seli; Rahayu, SE., MS, Dr. Mintarti (Jurnal Ilmiah Mahasiswa FEB, 2012)
Background of this study aimed to determine the vision, mission and goals of the Triseason Holiday, analyzing strengths, weaknesses, opportunities and threats of Triseason Holiday and conduct marketing strategy planning Triseason Holiday to gain competitive advantage. The data analysis technique used is qualitative analysis. Triseason Holiday Tour and Travel has great potential to grow and develop. This is shown by the aspects of the internal forces that is cooperation, low price, high quality, hospitality and comfortable services, tour guide fluently with foreign languages, legal and provide insurance to consumers. Companies just do marketing via internet marketing course that is less effective for the targeted segment of the secondary market as a private company and government institution it should be a consideration for companies in the future. Keywords: Marketing strategic planning, Competitive advantage, Triseason Holiday